SOCIAL ASPECTS OF INVESTMENT - V. V. Khrapkina; O. V. Veretennikova (Финансы: теория и практика, 2017)
The article substantiates the necessity to investigate the issue of socialization of economic relations and, in particular, the issue of social investment. It reviews some aspects of social investment theory and reports the current status of economic thought in this field. The conducted research based on a gnoseological approach proves that in modern conditions social investment as to its essence and nature is a complex category integrating economic and social behavior motives of the subjects, their goal set; tools used by investors and participants of investment activities, and the norms of behavior of all players. The research sets out main characteristics of social investment which in fact fall into the category reflecting relations between the subjects involved in investment activities aimed at solving social and economic problems.